Hepatic irradiation persistently eliminates liver resident NK cells. - Ryosuke Nakano; Masahiro Ohira; Takuya Yano; Yuki Imaoka; Yuka Tanaka; Hideki Ohdan (PLoS ONE, 2018)
Hepatic irradiation for the treatment of hepatobiliary malignancies often indirectly damages liver tissue and promotes the development of liver fibrosis. However, little is known concerning the effects of hepatic irradiation on the liver immune system, including natural killer (NK) cells. The aim of this study was therefore to investigate how hepatic irradiation influences the functions and characteristics of liver resident NK cells. An established murine hepatic irradiation model was used to examine the specific effects of hepatic irradiation on immune cell populations and metastasis. This analysis demonstrated that hepatic irradiation decreased the number of liver resident NK cells (DX5-TRAIL+), but did not affect the total NK number or proportions of NK cells in the liver or spleen. This effect was correlated with the hepatic irradiation dose. Surprisingly, the liver resident NK population had not recovered by two months after hepatic irradiation. We also found that hepatic irradiation limited the cytotoxic effects of liver-derived lymphocytes against a mouse hepatoma cell line and promoted hepatic metastases in an in vivo model, although adoptive transfer of activated NK cells could alleviate metastatic growth. Finally, we demonstrated that hepatic irradiation disrupted the development of liver-resident NK cells, even after the adoptive transfer of precursor cells from the bone marrow, liver, and spleen, suggesting that irradiation had altered the developmental environment of the liver. In summary, our data demonstrated that hepatic irradiation abolished the DX5-TRAIL+ liver-resident NK cell population and dampened antitumor activities in the liver for at least two months. Additionally, hepatic irradiation prevented differentiation of precursor cells into liver-resident NK cells.